(untitled) (World Economics and Finance Bulletin, 2022)
In the article, the comparative analysis and problems of the role of excise tax in the formation of state budget revenues in the Republic of Uzbekistan are researched, and its specific features are scientifically justified. Possibilities of improving the practice of taxation of excise goods in the tax system of the Republic of Uzbekistan were studied and recommendations were developed.